2005
DOI: 10.1002/cpp.454
|View full text |Cite
|
Sign up to set email alerts
|

Can patients specify treatment parameters? a preliminary investigation

Abstract: In this paper I provide data that were obtained when patients made decisions regarding the scheduling of treatment sessions. I outline relevant information from the literature and describe Perceptual Control Theory as the theoretical basis of this work. The implications and limitations of the data are discussed as well as suggestions for future research. The data are interpreted as preliminary evidence that patients can take responsibility for decisions made during psychological treatment programs.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
21
1
1

Year Published

2008
2008
2021
2021

Publication Types

Select...
6
3

Relationship

4
5

Authors

Journals

citations
Cited by 31 publications
(24 citation statements)
references
References 27 publications
1
21
1
1
Order By: Relevance
“…This system has proven to be useful in coding over a hundred clinical sessions with different clients and problems, while maintaining appropriate reliability standards. The results of our work so far suggest that the hypothetical functions of therapist's vocal behavior show systematic changes through the intervention process that are independent of the therapist, the client and the behavioral problem at hand, in contrast to what other authors and studies suggest (Beutler & Clarkin, 1990;Beutler et al, 2004;Blatt, Zuroff, Hawley, & Auerbach, 2010;Carey, 2005). This approach allows a first general model of the therapeutic process through the distribution of the therapist's behavior through the stages of psychological treatment.…”
Section: Introductioncontrasting
confidence: 72%
“…This system has proven to be useful in coding over a hundred clinical sessions with different clients and problems, while maintaining appropriate reliability standards. The results of our work so far suggest that the hypothetical functions of therapist's vocal behavior show systematic changes through the intervention process that are independent of the therapist, the client and the behavioral problem at hand, in contrast to what other authors and studies suggest (Beutler & Clarkin, 1990;Beutler et al, 2004;Blatt, Zuroff, Hawley, & Auerbach, 2010;Carey, 2005). This approach allows a first general model of the therapeutic process through the distribution of the therapist's behavior through the stages of psychological treatment.…”
Section: Introductioncontrasting
confidence: 72%
“…More information about MOL than what is provided here can be found elsewhere (Carey, 2005;Carey, 2006;Runkel, 2003).…”
Section: Considering Psychotherapymentioning
confidence: 93%
“…The principles of PCT suggest that people function best when they are able to control what happens to themselves so we endeavoured to maximize the extent to which this could occur by providing patients with the responsibility for the duration and frequency of their treatment program. This approach had been trialled successfully elsewhere (Carey, 2005;Carey & Mullan, in press). …”
Section: Settingmentioning
confidence: 96%
“…A number of case studies and pragmatic uncontrolled trials in routine practice have shown moderate to strong effect sizes for reductions in standardized measures of psychological distress after MOL. These clients have experienced a range of problems including depression, substance addictions, suicide attempts, bereavement, panic disorder, generalized anxiety disorder, social phobia, post-traumatic stress disorder, agrophobia, Asperger's disorder, relationship breakdowns, anger management, and eating disorders (Carey, 1999(Carey, , 2001(Carey, , 2005Carey, Carey, Mullan, Spratt, & Spratt, 2009;Carey & Mullan, 2008). Recently, a study of 51 patients in secondary care revealed that MOL was particularly efficient in producing beneficial outcomes, compared to an array of comparable psychological interventions (Carey, Tai, & Stiles, 2013).…”
Section: A Transdiagnostic Approach To Cbt Using Methods Of Levelsmentioning
confidence: 99%